Fabrication of Metal–Organic Frameworks inside Silica Nanopores with Significantly Enhanced Hydrostability and Catalytic Activity - Kou, Jiahui; Sun, Lin-Bing (ACS applied materials & interfaces, 2018)
Because of their diverse structure, high porosity, and tunable functionality, metal–organic frameworks (MOFs) are of great interest for diverse applications, including catalysis. However, the poor hydrostability of most reported MOFs hinders their catalytic applications seriously. In addition, the development of an effective method to improve the catalytic activity of MOFs is another challenge. Here, we report for the first time the development of a double-solvent strategy to fabricate MOFs inside silica nanopores. A typical MOF (MOF-5) and a mesoporous silica with two-dimensional hexagonal pore regularity (SBA-15) were first attempted. The double-solvent strategy is based on a hydrophobic solvent and a hydrophilic solution containing MOF precursors with a volume equal to or less than the pore volume of the support so that the MOF can be formed selectively in the channels of support. Our results show that upon confinement in silica nanopores the hydrostability of MOF-5 is apparently improved. The framework of MOF-5 is destroyed obviously in a humid environment for 15 min, but that confined in SBA-15 is well preserved after 8 h. Moreover, the catalytic activity of the composite MOF-5@SBA-15 is superior to that of pure MOF-5 regarding activity and reaction rate. Under the catalysis of MOF-5@SBA-15, the conversion of benzyl bromide in the Friedel–Crafts alkylation reaction can reach 100% at 80 °C for 3 h, which is much higher than that of pure MOF-5 (61%) and SBA-15 (0%). We also demonstrate that the double-solvent strategy can be successfully extended to other MOFs, such as HKUST-1 and ZIF-8. Our work might open up an avenue for the improvement of stability and performance of MOFs, which is highly expected for a variety of applications.